Rancang Bangun Boost Converter - Dwi Harselina; Hendri Hendri (Universitas Negeri Padang, 2019)
In the current technological advances, the use of power electronic converter technology has been widely used in everyday life. One example is the application of a DC converter with the Boost Converter method. This Boost Converter system is one of the nonisolated switching type DC regulators that can be used as a need for a voltage source in the direction of the variable output voltage, the value of the output voltage can be adjusted to be greater than the input voltage value. To design Boost Converter this requires several main components including the ATmega 328 microcontroller which functions as a control system, mosfet, and power supply. Based on the results of research conducted that the Boost Converter output can increase the voltage variable from 48VDC to 250VDC. With a source of 48 VDC, motor load, the output voltage is 100VDC, 120VDC, 140VDC, 160VDC, 180VDC.